Macronutrient Deficiencies in Citrus: Calcium, Magnesium, and Sulfur - Mongi Zekri; Thomas Obreza (EDIS)
This document is SL 202, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First printed: January 2003.